2016
DOI: 10.1080/02791072.2016.1188225
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ayahuasca and its Alkaloids on Drug Dependence: A Systematic Literature Review of Quantitative Studies in Animals and Humans

Abstract: Recently, the anti-addictive potential of ayahuasca, a dimethyltryptamine(DMT)- and β-carboline-rich hallucinogenic beverage traditionally used by indigenous groups of the Northwest Amazon and currently by syncretic churches worldwide, has received increased attention. To better evaluate this topic, we performed a systematic literature review using the PubMed database to find quantitative studies (using statistical analysis) that assessed the effects of ayahuasca or its components in drug-related symptoms or d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 55 publications
1
52
1
6
Order By: Relevance
“…As previously mentioned, ayahuasca consumption has been increasing and spreading all over the world, in some cases due to its reported health benefits [14,18]. In fact, some studies have described that, following a single dose of the drink, a rapid decrease in depressive symptoms is observed, which can last up to three weeks [19,20]. Other studies revealed that ayahuasca intake can significantly diminish anxiety and panic states [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…As previously mentioned, ayahuasca consumption has been increasing and spreading all over the world, in some cases due to its reported health benefits [14,18]. In fact, some studies have described that, following a single dose of the drink, a rapid decrease in depressive symptoms is observed, which can last up to three weeks [19,20]. Other studies revealed that ayahuasca intake can significantly diminish anxiety and panic states [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The ayahuasca-induced introspective experience has been shown to have potential benefits for the improvement of several pathologies such as addiction (Nunes et al, 2016;Thomas et al, 2013;Fernández et al, 2014), treatmentresistant depression (Osório et al, 2015;Sanches et al, 2016) and suicidal and aggressive behavior (Frecska, 2008;Grob et al, 1996). Ayahuasca also displays potential mental health protection (Bouso et al, 2012;Grob et al, 1996;Halpern et al, 2008), improved neuropsychological functions (Bouso et al, 2012Bouso et al, 2013) and improved creativity (Frecska et al, 2012;Kuypers et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical studies and observational studies of ayahuasca users suggest that ayahuasca has anxiolytic, antidepressive and antiaddictive effects (Table 3) 21,34,[37][38][39][40] . Regarding anxiolytic and antidepressive effects in humans, a double-blind, placebo-controlled studies with nine experienced ayahuasca users showed that a single ayahuasca dose was associated with less panic symptoms and reduced hopelessness 41 .…”
Section: Therapeutic Potentialsmentioning
confidence: 99%
“…For instance, recent studies with LSD and psilocybin for depression and anxiety in patients with life-threatening cancer reported promising results, and ayahuasca could also be evaluated in this clinical population 44,46,47 . Regarding drug dependence, although there is evidence from animal studies and from anecdotal reports and uncontrolled studies suggesting that ayahuasca has antiaddictive properties 21,38,40,48,49,54,57 , no controlled trials were ever performed and they are urgent needed.…”
Section: Suggestions For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation